Donor-acceptor random copolyesters containing perylenebisimide (PBI) and oligo(p-phenylene vinylene) (OPV) by melt condensation polymerization: energy transfer studies - Nisha, S. Kumari; Asha, S. K. (Journal of Physical Chemistry B, 2013)
Novel copolyesters consisting of oligo(p-phenylene vinylene) (OPV) as donor (D) and perylenebisimide (PBI) as acceptor (A) were synthesized by melt polycondensation. Photoinduced energy transfer and photoinduced charge separation in these polyesters were studied in solution as well as in the solid state. Selective excitation of OPV moiety resulted in the energy transfer with >90% efficiency from OPV to PBI chromophore in the solution state. The direct excitation of PBI in the D A copolyester resulted in reduced fluorescence emission of acceptor, indicating electron transfer between the D and A moieties. The effect of distance between donor and acceptor on the energy transfer efficiency from donor to acceptor was studied. Compared to a physical mixture of D and A polyesters alone, the energy transfer was 4 times more efficient in the D A copolyester, highlighting the influence of covalently linking D and A in a single polymer chain. A strong fluorescence quenching (similar to 100%) of both chromophores in solid state indicated an efficient photoinduced charge transfer after photoexcitation of either D or A. Thus, OPV-PBI main chain copolyester is an excellent system for the study of energy- and electron-transfer processes in organic semiconductor. Reactive blend of D/A copolyester was also prepared by the transesterification reaction between D and A alone copolyesters. The energy transfer efficiency from D to A moiety upon selective excitation of D chromophore in the D/A copolyester blend was similar to 4 times higher compared to a physical mixture of D and A alone copolyesters, which gave direct proof for the transesterification reaction in polyester/polyester reactive blending.